Tourism in the Philippines applied management perspectives (Gateway East, Singapore Springer Nature Singapore Pte Ltd., 2022)
"This edited book serves as the first instalment of a two-part title that aims to provide an academic exploration of the contemporary issues and perspectives on tourism in the Philippines. With a strong geographical focus, this book is the first country-focused volume under the series, Perspectives on Asian Tourism. Comprised of chapters based on conceptual and empirical research, this book aims to develop a foundational and practical knowledge base on Philippine tourism management. The chapters cover a range of national, regional, and local tourism management issues that cut across the following themes:• Governance issues in Philippine tourism destinations• The Tourism Act of 2009 • Tourism impacts and sustainability• Innovative tourism development strategies• Tourism marketing campaigns (i.e., It's More Fun in the Philippines!)• Philippine tourism and the ASEAN integration• Tourism and hospitality education in thePhilippinesThe contributions are drawn from the works of Filipino academics based in the Philippines and overseas institutions, and international academics researching tourism issues in the Philippines. The chapters are informed by a diverse set of disciplines including, but not limited to tourism studies, hospitality management, marketing, human resources management, public policy, environmental management, community development, and education.
This edited book is divided into four parts: first, an introduction to the development of policy and contemporary management issues in Philippine tourism; second, nature-based tourism and the natural environment; third, product development and branding; and fourth, accreditation and industry standards. The volume culminates with a synthesis of the progress of Philippine tourism development and management implications using the cases and experiences outlined in the chapters. This book serves as a systematic guide tothe current state of tourism development and management in the Philippines, and as essential reading for undergraduate and postgraduate students, researchers, educators, and, more importantly, tourism policy-makers." --
Part I. Introduction.- ​Chapter 1. Tourism in the Philippines: Overview of Policy Development and Management Issues.- Part II. Managing and Developing Philippine Tourism Destinations.- Chapter 2. Mandatory Accreditation of Primary Tourism Enterprises in the Philippines:Challenges in Enforcement.- Chapter 3. How could the Philippine Government Improve its Tourist Information Centres?.- Chapter 4. “Your Islands and Valley of Fun” – Cagayan Valley’s Journey to a Regional Brand.- Chapter 5. Culinary Tourism as an Avenue for Tourism Development: Mapping the Flavours of the Philippines.- Part III. Managing Tourism in the Natural Environment.- Chapter 6. Pursuing Sustainable Tourism in the Philippines through an Effective Ecotourism Strategy.- Chapter 7. Dealing with Socio-Ecological Problems in a Rapidly Growing Tourism Destination: A Case Study from El Nido, Palawan.- Chapter 8. Empowering People’s Organisations in Mangrove Forest Tourism Development: The Case of Infanta, Quezon.- Chapter 9. The ASEAN Common Competency Standards for Tourism Professionals (ACCSTP) and Common ASEAN Tourism Curriculum (CATC) in the Philippines: Status, Progress and Gaps.- Chapter 10. Towards a Competency Model of Tourism Officers in the Philippines: A Phenomenological Approach.- Chapter 11. Competencies for a Career in the Hospitality Industry in the Philippines in 2030: Towards Embracing The 4th Industrial Revolution.- Chapter 12. Rethinking Tourism Education in the Philippines.- Chapter 13. Decolonising Philippine Tourism and Hospitality Curricular Programmes.- Part V. Conclusion.- Chapter 14. Tourism in the Philippines: Suggestions for Policy Development and Management Issues.
Includes bibliographical references
Keywords: Aquino, Richard S; Porter, Brooke A; Tourism -- Philippines; Tourism -- Management; Sustainable tourism -- Philippines